2014
DOI: 10.1155/2014/261349
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effectiveness of Microlubrication Using a Vegetable Oil-Based Metal Working Fluid during End Milling AISI 1018 Steel

Abstract: Microlubrication minimizes the exposure of metal working fluids to the machining operators leading to an economical, safer, and healthier workplace environment. In this study, a vegetable oil-based lubricant was used to conduct wear analysis and to analyze the effectiveness of microlubrication during end milling AISI 1018 steel. A solid carbide cutting tool with bright oxide finish was used with varying cutting speed and feed rate having a constant depth of cut. Abrasion was the dominant wear mechanism for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The high lubricating property of coconut oil is due to the fundamental composition of the vegetable oil molecules as well as the chemical structure of oil itself [53]. SE recorded slightly lower cutting temperature compared to MJO1 and MJO3.…”
Section: Temperaturementioning
confidence: 97%
See 1 more Smart Citation
“…The high lubricating property of coconut oil is due to the fundamental composition of the vegetable oil molecules as well as the chemical structure of oil itself [53]. SE recorded slightly lower cutting temperature compared to MJO1 and MJO3.…”
Section: Temperaturementioning
confidence: 97%
“…The effectiveness of micro lubrication was analyzed using a vegetable oil-based metalworking fluid during end milling AISI 1018 steel and it is possible to obtain higher tool life [53]. A comparable flank wear is seen under formulated Sunflower, Soybean, Canola, and Palm oil based soluble cutting fluid compared to mineral oil during milling [54].…”
Section: Tool Wearmentioning
confidence: 99%
“…There have been numerous studies on micro or meso milling using MQL and dry machining. For example, [9] studied the micro-milling using MQL with varying the cutting parameters and analyzed the tool performance and machined surface condition. The tool performance was analyzed by [5] and it showed that MQL increased the tool life by 100 times compared to dry machining.…”
Section: Introductionmentioning
confidence: 99%
“…However, it requires special machining and cutting tool setups [11,13,14]. MQL, known as the "micro-lubrication" and "near-dry machining" [15,16], refers to a small amount of cutting fluid (2-100 ml/hr) in the form of aerosol being delivered to the tool-to-workpiece interface. MQL may also refer to use of cutting fluids in tiny quantities [12,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…MQL, known as the "micro-lubrication" and "near-dry machining" [15,16], refers to a small amount of cutting fluid (2-100 ml/hr) in the form of aerosol being delivered to the tool-to-workpiece interface. MQL may also refer to use of cutting fluids in tiny quantities [12,15,17]. The lubricant does not recirculate through the lubrication system since it is almost all evaporated at the point of application.…”
Section: Introductionmentioning
confidence: 99%